using boolean algebra simplify following (overline A + B)(A+C)
Question
using boolean algebra simplify following
Solution
Sure, let's simplify the given Boolean expression step by step.
Given expression: (A' + B)(A + C)
Step 1: Apply the distributive law, which states that A(B + C) = AB + AC.
So, (A' + B)(A + C) = A'A + A'C + BA + BC
Step 2: Apply the law of complementation, which states that AA' = 0.
So, A'A + A'C + BA + BC = 0 + A'C + BA + BC
Step 3: Apply the law of identity, which states that A + 0 = A.
So, 0 + A'C + BA + BC = A'C + BA + BC
So, the simplified Boolean expression is A'C + BA + BC.
Similar Questions
using boolean algebra simplify following (overline A + B)(A+C)
Simplify the following expressions using Boolean algebra:a) (AB’C’ + AB’C + ABC + AB’C) (A + B)
Use a Karnaugh map to reduce each expression to a minimum SOP form:(a) A + B(overline C) + CD
Using Boolean laws simplify each of the following propositions:a. a ∧ b ∨ a ∧ ¬b
2) What is the simplest Boolean expression equivalent to A’B’C + ABC’?A) A’CB) A’ + CC) A’C’D) AC
Upgrade your grade with Knowee
Get personalized homework help. Review tough concepts in more detail, or go deeper into your topic by exploring other relevant questions.